Attitude Relationship With The Role of Family In Providing Asi Assembly Food - Hengki Irawan; Erna Susilowati (Akademi Keperawatan Dharma Husada Kediri, 2018)
The feeding of babies is mostly determined by the mother. The role of the mother is shaped by the knowledge and attitudes of the mother and her family. The attitude of mothers regarding feeding to children is a factor that determines a person to behave and plays a role in providing the right food for children. Aging in this study is to determine the relationship between maternal attitudes and the role of mothers in providing complementary foods. This study was conducted on 50 mothers who have children aged 6-12 months in the posyandu area of ​​the Lirboyo village in the Campurejo Community Health Center area. The time for conducting the research is 3 months, namely June to August 2018. This study uses the Cross Sectional method. The independent variable in this study is the attitude of the mother. The dependent variable in this study is the role of mothers in providing complementary food for breast milk. Data collection using Quasioner. The data obtained were analyzed using SPSS to identify data on attitudes and roles of mothers in the supply of ASI complementary foods, using the Spearman Rho test to see the relationship between attitudes and maternal roles, a significant level of p <0.05. The results showed that there was a relationship between attitudes and the role of parents in providing complementary ASI foods (p = 0.00) Communities and respondents were expected to be able to apply the knowledge gained through proper self-care and provide knowledge to others who did not know it, so It is expected that the community will also participate in helping create a conducive environment for child development. Keywords: Attitudes, Roles, ASI Companion, Family